COEXISTENCE OF CERIUM(III)/(IV) IN PHOSPHATE AND MOLYBDATE MELTS - Zozulia, Valeria; Slobodyanik, Mykola; Ushchapivska, Tetiana; Terebilenko, Kateryna (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2025)
For the first time, the possibilities of controlled in fluence on the valence states of ceriumin phosphate and molybdate melts have been systematically analyzed. A series of molybdates with a scheelite structure, MICe(MoO4)2 (MI – Li, Na, K, Cs), were obtained by crystallization from melt solutions, and the crystallization regions of Na3Ce(PO4)2 were established. The role of the acidity of molybdate, phosphate-molybdate, and fluoride-phosphate melts in the stability of cerium compounds in different oxidation states was determined for the first time. The role of acidity in molybdate, phosphate-molybdate, and fluoride-phosphate melts on the stability of cerium compounds in various oxidation states has been established. In more acidic melts corresponding to the salts MI2Mo3O10 and MI2Mo2O7 (MI = Li, Na, K, Cs) with low M/Moratios (0.5–0.8), stabilization of the lower oxidation state of cerium (III) is observed. To optimize the conditions for obtaining monocrystalline doublephosphate Na3Ce(PO4)2 under milder conditions and at lower temperatures, we selected two systems: Na2O–P2O5–NaF and Na2O–P2O5–MoO3. The salts NaF and Na2MoO4 were chosen because their presence in phosphate melts is one of the factors that depolymerize phosphate tetrahedra and lower the melting temperature of the corresponding batch due to the formation of low-melting eutectics. Thus, with a sodium fluoride content ranging from 30 to 60 mol.%, the exclusive formation of Na3Ce(PO4)2 is observed. Thus, during spontaneous crystallization from fluoridemelts, the Na/P ratio plays a decisive role, while the influence of the fluoride component becomes structurally formative at NaF concentrations between 30 and 60%. Conversely, with an increase in the content of alkali elements in the molten salts, the formation of a phase with a high eroxidation state of cerium in the form of CeO2 occurs. The established pattern can be used to obtain a broader range of inorganic compounds based on cerium (III).